Modeling of a PEM Fuel Cell Electric Bus with MATLAB/Simulink - Dakurah, John Evans; Solmaz, Hamit; Kocakulak, Tolga (Automotive Experiences, 2024)
There have been great strides in recent years in the shift from conventional Internal Combustion Engine Vehicles (ICEVs) because of the deteriorating effects the fossil fuels they use have on the environment. Although lithium-ion battery electric vehicles (EVs) address some of these environmental problems, they do not appear to be a promising alternative because of their limited range, long charging duration, and the negative effects resulting from the production and disposal of their batteries. Demand for hydrogen vehicles has therefore increased over the years. This is because, since they use hydrogen as a fuel, they offer longer ranges, shorter refueling durations, and zero emissions. In this paper, a 70 kW PEM Fuel Cell Electric Bus (PEMFCEB) which has a 50 kWh buffer battery, and a total hydrogen capacity of 38 kg is modeled using MATLAB/Simulink. In the study, two hybrid energy management systems – fuzzy logic and conventional on-off using a ‘Relay’ block – are integrated into the model. By simulating several repeated NEDC (New European Driving Cycle) and WLTP (Worldwide Harmonized Light Vehicle Test Procedure) cycles, the overall performance of the bus including its total range, consumption of hydrogen and oxygen, and fuel cell efficiency under each energy management system is analyzed and compared. For instance, during the NEDC cycle, the bus achieves a total range of 492.02 km with Fuzzy Logic compared to 448.85 km with the traditional on-off system. Similarly, under the WLTP cycle, the bus exhibits a total range of 407.61 km and 362.33 km with Fuzzy Logic and on-off techniques respectively.